Unveiling motives for dentistry studies: psychometric validation of a comprehensive questionnaire among aspiring dental students - Jorge Moncayo-Rizzo; Geovanny Alvarado-Villa; Iván Cherrez-Ojeda; Juan Carlos Gallardo; Eleonor Velez Leon; Susana Patricia Gonzalez Eras (Nature Publishing Group, 2024)
Abstract Objective The aim of this study is to develop and validate a questionnaire for dental students in Ecuador to assess their reasons to study dentistry. Materials and methods A 25-item questionnaire was developed by the authors based on similar studies and a qualitative study. The questionnaire had five theoretical factors: economic, professional, vocational, social and academic reasons for study. In the first two samples, exploratory factor analysis was performed to identify the structure, and the models obtained were compared with confirmatory factor analysis in the third sample. Results Three samples were used, sample A with 201 participants, sample B with 623 participants, and sample C with 596 participants. Two-thirds of the participants were female and almost one-third were from coast region. The EFA applied in sample A resulted in a five-factor model with 18 items; in contrast, a three-factor model was obtained from sample B. According to the CFA in sample C, the best model was explained by three factors: labor, vocational and academic reasons. Considering two items to cross-load in labor and vocational factors, which are theoretically justified. Conclusion This study presents a 12-item questionnaire that assesses labor, vocational and academic reasons for studying dentistry in an Ecuadorian population.